Sterility Assessment Strategy for Cell-Based Medicinal Products: A Review of International Regulatory Approaches - M. V. Roschina; O. V. Gunar (Regulatory Research and Medicine Evaluation, 2026)
INTRODUCTION. Cell-based medicinal products are among the most complex biomedical medicinal products, with manufacturing processes associated with a high risk of microbial contamination and the impossibility of terminal sterilization. Ensuring the sterility of these products requires the implementation of a comprehensive risk-based microbiological control system throughout all stages of the manufacturing process. AIM. A review of current approaches to developing a sterility assessment strategy for cell-based medicinal products. DISCUSSION. The analysis demonstrated that conventional pharmacopeial sterility testing approaches have limited applicability to cell-based medicinal products due to their short shelf life, limited sample volume, and the interference of cellular components with microbiological test results. The major sources of contamination are starting biological material, personnel, the manufacturing environment, equipment, culture media, and transportation stages. Current international GMP, EMA, FDA, PIC/S, and EAEU requirements are focused on the implementation of a contamination control strategy, continuous monitoring of aseptic processes, and a risk-based approach. Alternative rapid microbiological methods are becoming increasingly important, as they significantly reduce the time required to obtain results and improve the speed of batch release decision-making. CONCLUSIONS. The modern strategy for sterility assessment of cell-based medicinal products should be based on an integrated microbiological risk management system that incorporates aseptic manufacturing, monitoring of critical process parameters, a contamination control strategy, and the use of validated alternative microbiological testing methods. Such an approach improves the reliability of microbiological safety assurance for cell-based medicinal products throughout all stages of their manufacturing and clinical application.